Antioxidant Activities of Extracts of Trengguli Stem Bark (Cassia fistula L.) - Hermien Noorhajat (IJENS Publishers, 2012)
This research is conducted to examine the antioxidant activity on the extract of stem bark C.fistula. The antioxidant activities of C.fistula stem bark extract were evaluated with lipid peroxides test using ferric thiosyanat method (FTC) and 2.6-di-t-butyl-4-metilfenol (BHT) as standard equivalent antioxidant capacity. C.fistula stem bark maceration successively used solvent normal heksane (non polar), ethyl acetate (semi-polar) and methanol (polar). The etyl acetate extract (Ea) shows higher antioxidant activity than the n.hexane extract (Hx) and methanol extract (MeOH). Therefore, the sequence of antioxidant activity is as follows ethyl acetate extract > methanol extract > n.hexane extract, with antioxidant activity consecutively at 5 hours: 65.98%, 58.19% and 32.66%. Those amount are equivalent to the standard synthetic antioxidant BHT (100 ppm), which causes 95.7% antioxidant activity (in 5 hours) inhibition of linoleic acid peroxidation. There is a connection between antioxidant activity of an extract with the content of the total phenol in each extract. From the assay of phenolic extracts with the method of Folin-Ciocalteu reagent (FCR) and also using afzelechin standard as a comparision, we find that the ethyl acetate extract has the highest total phenolic where the entire sequences are as follows: Ea> MeOH> Hx. with total phenol content consecutive 177.55, 123.2167, 7.433333